2019
DOI: 10.3390/s19051097
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Fiber Optic Sensor, Based on the Fabry–Perot Interference, Assisted with Fluorescent Material for the Simultaneous Measurement of Temperature and Pressure

Abstract: Herein we design a fiber sensor able to simultaneously measure the temperature and the pressure under harsh conditions, such as strong electromagnetic interference and high pressure. It is built on the basis of the fiber-optic Fabry–Perot (F–P) interference and the temperature sensitive mechanism of fluorescent materials. Both halogen lamps and light-emitting diodes (LED) are employed as the excitation light source. The reflected light from the sensor contains the low coherent information of interference cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Conversely, another study showed no difference between HAL and LED LCUs in generating heat (Drost et al, 2019). These different results in the literature may be related to the kind of temperature sensor and the methodology used (Jiang et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, another study showed no difference between HAL and LED LCUs in generating heat (Drost et al, 2019). These different results in the literature may be related to the kind of temperature sensor and the methodology used (Jiang et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Conventional silicon diaphragm-based FP cavities are made of Pyrex glass and assembled using an anodic bonding process, which has the advantage of low-temperature bonding processing [ 43 , 44 , 45 , 46 , 47 ]. The pressure sensitivity can be easily adjusted by designing the thickness of the silicon diaphragm and the microcavity diameter.…”
Section: Different Materials Of Mems Fp Pressure Sensor Diaphragmsmentioning
confidence: 99%
“…In addition, since some gases are released during anodic bonding, which will affect the effect of vacuum bonding, researchers have developed metal bonding such as Au/Au thermal compression bonding [ 46 ]. In addition, researchers have also developed techniques including dual FP [ 44 ], fiber grating [ 45 ], or temperature-sensitive fluorescent materials [ 47 ] for in situ temperature measurement. In 2014, Yin et al [ 44 ] presented a silicon–glass–silicon sandwich structure, constructing two serially connected FP cavities.…”
Section: Different Materials Of Mems Fp Pressure Sensor Diaphragmsmentioning
confidence: 99%
“…Compared to many traditionally used electric sensors such as thermocouples and thermal resistances [19,20], optical fiber temperature sensors become one of the most commonly used tools because of their distinctive advantages as small sizes, long-range sensing, immunity to electromagnetic interference, resistance to environments, and distributed sensing networking potentials [21,22]. Therefore, many optical fiber temperature sensors have been investigated and used in various applications, such as fiber Bragg grating [23], photonic crystal fibers [24], and Fabry-Perot fiber sensors [25,26]. Here, in our work, we prepared three solid discs of fluorescein derivatives dyes of different covalent bonds in polymeric host to explore the impact of different connections of covalent bonds between fluorescence probe and polymer chain on temperature sensing.…”
Section: Introductionmentioning
confidence: 99%